LIFE CYCLE ASSESSMENT (LCA): ENERGI DAN EMISI PADA PENANGKAPAN DAN PENGALENGAN IKAN (Study Kasus Pada CV. Pasific Harvest, Muncar Banyuwangi) - , MIFTAHUL CHOIRON, Dr. Ir. R. Wahyu Supartono ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Energy is absolutely necessary in an industrial activity. High efficiency in energy consumption will increase the competition of industry. The aim of this study was to evaluate energy consumption and gases emission from catch and canned fish production in CV.Pasific Harvest, Banyuwangi, Indonesia. LCA is use to analyze energy consumption and gases emission released by fish canning industry. It has four main steps to complete the LCA method